Relationship of Cover Percentage Coral Reef and Fish Abundance in The National Marine Park of Wakatobi - Dian Sutono (Jurnal Perikanan dan Kelautan, 2016)
Coral reef ecosystem is a marine resources that have some important role in supporting the life of a variety of aquatic organisms, such as shelter, feeding ground, and breeding ground for a large marine biota. This research was conducted in February - May 2015 in the conservation area National Marine Park of Wakatobi. This study to determine of percentage of live coral covering, fish abundance with coral reefs associated, to know the environmental factors to the lives of aquatic biota, as well as to analyze the relationship between the percentage of live coral cover with an abundance of reef fish in the waters of Kapota Island, which is included in the National Marine Park of Wakatobi. The results showed that the average value of live coral cover in the waters of the research area of 47.77% (enter the category of medium) with an average abundance of reef fish as many as 195 individuals / 250 m2. Relationship of life coral and reef fish abundance are positive symbioses with 0.0184 value determinant (R2).